PROMOTIONAL PACKAGES OF KAMPOENG KOPI BANARAN - , KIKI MULIANA ISWATI, Supriyono, S.S., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Kampoeng Kopi Banaran is one of coffee plantation in Semarang regency. It was built in August 28, 2002. This place use many strategies to get the consumers and increase their sales. By using this promotional strategy, Kampoeng Kopi Banaran sell their promotional packages, facilities and activities in order to get the consumers. The aim of this graduating paper research is to know promotional strategy, fasilities and activities in Kampoeng Kopi Banaran. Methods of collecting data are direct observation and library research. In the field study, the writer interviews the manager and supervisor of Kampoeng Kopi Banaran in order to gather information about Kampoeng Kopi Banaranâs profile in a brief. For the library research, the writer reads some books, and articles from internet, which are related to the topic. Each products which are offered by store got a full attention from consumers. From the data writer collect prove that their promotional strategy is very appropriate to promote the product that they sell as well as their packages.